Pengaruh Health Education Menggunakan Video Animasi Terhadap Kebersihan Tangan dan Kuku pada Anak Sekolah Dasar di SDN Sekarputih 01 Bondowoso - Novalita Novalita; Hamim Hamim; Rizka Rizka (Jurnal Ventilator, 2024)
Hand hygiene is an important aspect in maintaining individual health and preventing the spread of disease, an effective practice for maintaining hand hygiene is washing hands regularly. Health education is an application of educational concepts in a learning process, namely health education using animated videos. This research aims to determine the effect of health education using animated videos on hand and nail hygiene in elementary school children at SDN Sekarputih 01 Bondowoso. The method in this research used a pre-experimental design with a one-group pre-post test approach. The population was 90 student respondents at SDN Sekarputih 01 Bondowoso, 73 samples studied were taken using purposive sampling. Data collection includes editing, coding, scoring, and tabulating. The instruments used are Animation Videos, SOPs, and Modules. The data obtained from this research was analyzed using the Wilcoxon Test. The results of this research showed that the cleanliness of hands and nails before being given health education using animated videos was mostly poor 31 (42.5%), after health education using animated videos was mostly very good 52 (71.2%), from the test results The Wilcoxon Signed Rank Test shows a value of p = 0.000 with ? = <0.05 (p = 0.000 with ? = <0.05) p is smaller than ?, then H0 is rejected and H1 is accepted, it can be concluded that there is an influence of health education using animated videos on hand hygiene and nails. It is hoped that respondents who has lack knowledge about washing hands and cutting nails can apply health education using animated videos very effective because animated videos have interesting advantages and can make respondents focus on their interest in the images displayed.